Characteristics of Dysregulated Proinflammatory Cytokines and Cognitive Dysfunction in Late-Life Depression and Amnestic Mild Cognitive Impairment - Nie, Jing; Fang, Yuan; Chen, Ying; Aidina, Aisikeer; Qiu, Qi; Zhao, Lu; Liu, Xiang; Sun, Lin; Li, Yun; Zhong, Chuwen; Li, Yuan; Li, Xia (Frontiers in Immunology, 2022)
Background: Late life depression (LLD) and amnestic mild cognitive impairment (aMCI) are two different kinds of diseases associated with a high risk of developing Alzheimer's disease (AD). Both diseases are accompanied by dysregulation of inflammation. However, the differences and similarities of peripheral inflammatory parameters in these two diseases are not well understood. Methods: We used Luminex assays to measured 29 cytokines simultaneously in the plasma of two large cohorts of subjects at high risk for AD (23 LLD and 23 aMCI) and 23 normal controls(NC) in the community. Demographics and lifestyle factors were also collected. Cognitive function was evaluated with the Chinese versions of Montreal Cognitive Assessment(MoCA) and neuropsychological test battery (NTB). Results: We observed a remarkably increased level of IL-6 in the plasma, and reduced level of chemokines (CXCL11 and CCL13) in the LLD group in comparison to the aMCI group. The LLD group also showed lower levels of CXCL16 compared to the NC group. Furthermore, altered cytokine level was associated with abnormal results in neuropsychological testing and Geriatric depression scale scores in both LLD and aMCI groups. Notably, cytokines (IL-6 and CCL13) and two sub items of c-MoCA (orientation and short-term memory) combinations generating the best area under the receiver operating characteristics (AUROC=0.974). Conclusion: Novel model based on pro-inflammatory cytokines and brief screening tests performs with fair accuracy in the discrimination between LLD and aMCI. These findings will give new clues to provide new therapeutic target for intervention or a marker for two diseases with similar pre-dementia syndromes.